Palladium-catalyzed Heck cyclization/carbonylation with formates: synthesis of azaindoline-3-acetates and furoazaindolines. Issue 48 (26th May 2022) - Ye, Hao; Wu, Linhui; Zhang, Minrui; Jiang, Guomin; Dai, Hong; Wu, Xin-Xing
Abstract : A palladium-catalyzed domino cyclization/carbonylation has been achieved to access all four isomers of the azaindoline family bearing ester functional groups and furoazaindoline derivatives. Abstract : We report herein a palladium-catalyzed domino cyclization/carbonylation to access ester-functionalized azaindolines, applying formates as a convenient carbonyl source. All four azaindoline isomers were constructed, exhibiting good functional group compatibility. On this basis, modifying the starting tether on the aminopyridine led to furoazaindolines via an intramolecular reductive cyclization after the palladium-catalyzed process.